2012
DOI: 10.1136/vr.e5024
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular mast cell tumour in a dog

Abstract: The dog made an unremarkable recovery from surgery and there have not been any clinical signs of local or distant disease at the time of writing. We would be interested to hear from any colleagues who have seen a similar presentation of intramuscular mast cell tumours in the dog with a view to compiling a case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In that study, decreased survival was found with a mitotic count (MC) > 4/10 high power field (HPF; 2.37 sq mm), infiltrative growth pattern and the presence of multinucleation. 3 Intramuscular MCT (IntraM MCT) have been reported previously 4,5 and in a case series of seven dogs; three dogs were treated with surgery alone and 3 dogs with surgery and adjuvant chemotherapy postsurgery; no recurrence or metastasis were reported with a follow-up of 7 months. 5 Surgery is currently the treatment of choice for dermal, SC, and IntraM MCT.…”
Section: Introductionmentioning
confidence: 97%
“…In that study, decreased survival was found with a mitotic count (MC) > 4/10 high power field (HPF; 2.37 sq mm), infiltrative growth pattern and the presence of multinucleation. 3 Intramuscular MCT (IntraM MCT) have been reported previously 4,5 and in a case series of seven dogs; three dogs were treated with surgery alone and 3 dogs with surgery and adjuvant chemotherapy postsurgery; no recurrence or metastasis were reported with a follow-up of 7 months. 5 Surgery is currently the treatment of choice for dermal, SC, and IntraM MCT.…”
Section: Introductionmentioning
confidence: 97%
“…The signs of severe pain and turgid swelling raised concern for possible compartment syndrome in this dog. To our knowledge, there has been only 1 previous report 19 describing an intramuscular mast cell tumor in a dog.…”
Section: Discussionmentioning
confidence: 99%